Dampak Pembangunan Industri Terhadap Perubahan Penggunaan Tanah dan Kesesuaiannya dengan Tata Ruang (Studi di Kabupaten Semarang Provinsi Jawa Tengah) - Febsy Niandyti; Yendi Sufyandi; Westi Utami (Tunas Agraria, 2019)
Abstract: The industry has a great influence on the economy of Semarang Regency by becoming the largest contributor to Gross Regional Domestic Product (GRDP). The rapid industrial development from 2011-2017 has an impact on the decrease of agricultural land area, besides that industrial development has implication on land use mismatch of Spatial Plan. This study describes the results of descriptive qualitative analysis with spatial approach from the impact of industrial development on land use change and land use suitability for industry in 2017 against Spatial Plan. The analysis shows that, first, the impact of industrial development on land use change in Semarang regency in 2011-2017 resulted in the amount of agricultural land decreased by 253,32 Ha. The biggest land use change occurred on industrial land use that is 146,10 Ha (28,84%). Second, the use of land for industry in 2017 of 288,05 Ha has been in accordance with the spatial plan is in accordance with the industrial designation area, while the land with an area of 202,02 Ha is used for industries that are not in accordance with the industrial designation area. Keywords: Land Use Change, The Industry, The Suitability of The Spatial Plans Intisari: Industri telah memberikan pengaruh terhadap perekonomian Kabupaten Semarang dengan menjadi penyumbang terbesar pada Produk Domestik Regional Bruto (PDRB). Pesatnya perkembangan industri dari tahun 2011-2017 berdampak pada penurunan luas tanah pertanian, disamping itu perkembangan industri tersebut berimplikasi pada ketidaksesuaian penggunaan tanah tehadap Rencana Tata Ruang Wilayah (RTRW). Kajian ini menjelaskan mengenai hasil analisis secara deskriptif kualitatif dengan pendekatan keruangan dari dampak pembangunan industri terhadap perubahan penggunaan tanah serta kesesuaian penggunaan tanah untuk industri tahun 2017 terhadap RTRW. Hasil analisis menunjukkan bahwa pertama, dampak pembangunan industri terhadap perubahan penggunaan tanah di Kabupaten Semarang tahun 2011-2017 mengakibatkan jumlah luas tanah pertanian mengalami penurunan sebesar 253,32 Ha. Perubahan penggunaan tanah terbesar terjadi pada penggunaan tanah untuk industri yaitu seluas 146,10 Ha (28,84%). Kedua, penggunaan tanah untuk industri tahun 2017 seluas 288,05 Ha telah sesuai dengan RTRW yaitu sesuai dengan kawasan peruntukan industri, sedangkan tanah dengan luas 202,02 Ha digunakan untuk industri yang tidak sesuai dengan kawasan peruntukan industri. Kata Kunci: perubahan penggunaan tanah, industri, kesesuaian RTRW